Green Banking: How to Enhance Banking Policy on Sustainable Development, Renewable Energy, and Biodiversity in Indonesia: Case Study in Food and Energy Security Loan Role Models - NUR Hidayat (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2018)
Presently, financial crisis, energy crisis, food crisis, poverty, and global warming are the most complicated issue on the global economy. Indonesia faced on problems and challenges that are not much different, namely the declining export value, food security or the rising imports of basic foodstuffs, energy security, and the impact of global warmings such as crops production, flood, healthcare, and biodiversity. This paper reveals bank’s responsible for environmental damage in financing to their customers, whose have impacted on the environment. The data collected through, in-depth interviews and literature studies. The result of this research reveals that since the late 1970s, loans for food and agricultural intensification have been rolled out in Indonesia. It continues to adjust from year on year, it started from October 2007 was refined to Kredit Ketahanan Pangan dan Energi (KKP-E) (Food and Energy Security Loan). This is an effort to reach the necessity of main food in Indonesia, reduce the dependence of food imports and energy made from fossil fuels and develop other energy based biofuel source. The alternative energy here is based on cassava and sugar cane to become bioethanol. This fact that Indonesian banking has long contributed to a green economy as a new paradigm of sustainable development that balances people, profit, and a planet, which can be adopted by other developing countries, particularly agriculture-based.